The Role of Semantic Complexity in Treatment of Naming Deficits: Training Semantic Categories in Fluent Aphasia by Controlling Exemplar Typicality - Kiran, Swathi (2003)
The effect of typicality of category exemplars on naming was investigated using a single subject experimental design across participants and behaviors in 4 patients with fluent aphasia. Participants received a semantic feature treatment to improve naming of either typical or atypical items within semantic categories, while generalization was tested to untrained items of the category. The order of typicality and category trained was counterbalanced across participants. Results indicated that patients trained on naming of atypical exemplars demonstrated generalization to naming of intermediate and typical items. However, patients trained on typical items demonstrated no generalized naming effect to intermediate or atypical examples. Furthermore, analysis of errors indicated an evolution of errors throughout training, from those with no apparent relationship to the target to primarily semantic and phonemic paraphasias. Performance on standardized language tests also showed changes as a function of treatment. Theoretical and clinical implications regarding the impact of considering semantic complexity on rehabilitation of naming deficits in aphasia are discussed.